Comparison of the association between different dietary pattern scoring indices and periodontitis and their population heterogeneity - Zhang, Rui; Zhang, Zushan; Ji, Shuming; Yang, Wenjie; Long, Tengfei (Frontiers in Nutrition, 2025)
ObjectivesAssociation between different dietary indices and periodontitis remained unclear. This study aims to compare the associations of four commonly dietary indices (including Healthy Eating Index-2020, HEI-2020; alternative Mediterranean Diet Score, aMED; Dietary Approaches to Stop Hypertension, DASH; Dietary Inflammatory Index, DII) with the risk of periodontitis.MethodsA cross-sectional study was designed using a publicly available data collected from the National Health and Nutrition Examination Survey (NHANES) between 2009 and 2014 (N = 8,571 adults over 30 years). After adjusting for confounders, dietary indices were included in logistic regression models by single, double and overall forms to explore the association with periodontitis. Odds ratios (ORs) for the dietary indices were adjusted by one-fourth of their scoring range to compare the effect sizes; and diminishing marginal receiver operating characteristic (ROC) curves analysis with univariate exclusion in the overall model was used to compare the contribution of the dietary indices to periodontitis. Restricted cubic splines (RCS) was used to explore the non-linear association in both the total population and various sub-populations.ResultsAlthough all dietary indices exhibited a significant effect on periodontitis in single exposure model; only DASH and DII retained complete significance in the double exposure condition. In the overall model, aMED and DASH presented significantly positive associations, the corresponding OR were 1.147 (95%CI: 1.002–1.313) and 1.310 (95%CI: 1.139–1.507); but DII showed a negative association with OR of 0.675 (95%CI: 0.597–0.763). The ROC analyses showed that the contribution of dietary indices to periodontitis was second only to sex and ethnicity. The non-linear tests showed an approximately linear association for HEI-2020, aMED, and DASH, but a significant non-linear association for DII (p = 0.024). Subgroups of females, younger than 50 years old, non-Hispanic White, smokers, and the ratio of family income to poverty ≤ 2.4 were more consistent with the association found in the total population.ConclusionA poor habit for DASH was robustly linked to the occurrence of periodontitis, while the other three dietary patterns were not. Our research suggests that including the DASH index in the evaluation of periodontitis risk and implementing targeted prevention strategies may be beneficial.